Experimental Evaluation of Aerial Manipulation Robot in Contact With 15 kV Power Line: Shielded and Long Reach Configurations - Alejandro Suarez; Rafael Salmoral; Pedro J. Zarco-Perinan; Anibal Ollero (IEEE Access, 2021)
The use of aerial manipulators for the inspection and maintenance of the power grid requires the safe interaction of the robot with high voltage power lines. In order to identify possible faults or malfunctions during the approaching or interaction phases, this paper presents experimental results in a real 15 kV power line, considering four different configurations for the manipulator: 1) aluminum tube attached to the landing gear, 2) robotic arm attached to the multi-rotor base, 3) shielded aerial manipulator, and 4) long reach configuration (insulated). The paper investigates the electromagnetic susceptibility of the autopilot and the electronic speed controllers to the electrostatic discharge (ESD) raised when the manipulator touches the line, causing the momentary failure of the rotors. A model of the electromagnetic effects associated to the interaction with the line is provided, comparing later the effectiveness of the two solutions for the aerial manipulator: shielding, and insulation.